2020
DOI: 10.1016/j.nicl.2020.102354
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in resting state networks in early presymptomatic carriers of C9orf72 expansions

Abstract: Highlights Functional connectivity changes over 18 months in presymptomatic C9orf72 carriers. Thalamic networks have reduced functional connectivity, but are stable over time. Presymptomatic FC patterns trend toward those of symptomatic C9orf72 carriers. Reduced connectivity of posterior parietal regions occurs in different networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These trends in structural and functional alterations reinforce the hypothesis that the structural alteration of the pulvinar in C9orf carriers could be linked to the neurodevelopmental profile [46], which might lead a functional adaptation over time, even if reduced in some occipital–parietal regions, as we reported. This hypothesis is corroborated by the longitudinal observation of presymptomatic C9orf72 carriers in which the decrease of thalamic functional connectivity (MNI coordinates of thalamic seeds fall within the anterior seed of pulvinar) was stable over time [47]. It has been suggested that maintaining the topography of functional networks facilitates cognitive resilience in the face of ongoing structural changes in presymptomatic patients [16, 48, 49].…”
Section: Discussionmentioning
confidence: 86%
“…These trends in structural and functional alterations reinforce the hypothesis that the structural alteration of the pulvinar in C9orf carriers could be linked to the neurodevelopmental profile [46], which might lead a functional adaptation over time, even if reduced in some occipital–parietal regions, as we reported. This hypothesis is corroborated by the longitudinal observation of presymptomatic C9orf72 carriers in which the decrease of thalamic functional connectivity (MNI coordinates of thalamic seeds fall within the anterior seed of pulvinar) was stable over time [47]. It has been suggested that maintaining the topography of functional networks facilitates cognitive resilience in the face of ongoing structural changes in presymptomatic patients [16, 48, 49].…”
Section: Discussionmentioning
confidence: 86%
“…Gray matter findings are complemented by WM analyses that consistently capture anterior thalamic radiation changes in both ALS and ALS–FTD phenotypes (Bede et al., 2013 ; Floeter et al., 2016 ; Mahoney et al., 2012 ). Functional studies invariably detect reduced connectivity in thalamus‐seeded circuits (Shoukry et al., 2020 ) and the salience network (Lee et al., 2014 ). 18 FDG‐PET studies are consistent in identifying bilateral thalamic hypometabolism (Cistaro et al., 2014 ; Diehl‐Schmid et al., 2019 ; Soleimani‐Meigooni et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Memory is usually not early impaired in bvFTD and therefore has been less studied. Nevertheless, one study reported a positive correlation between memory performance and RSFC between the right anterior insula and the right precuneus in symptomatic C9orf72 mutation carriers (a mix of bvFTD and ALS) (Shoukry et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have found associations between FC and specific FTD‐related mutations (Lee et al., 2017 ; Shoukry et al., 2020 ; Tsvetanov et al., 2021 ; Whitwell et al., 2011 ), but there are also studies that failed to detect gene‐related changes in FC (Bouts et al., 2018 ; Pievani, Paternicò, et al., 2014 ). The influence of specific FTD‐related genes in FC is complex enough to warrant a separate review.…”
Section: Resultsmentioning
confidence: 99%